Translational termination in Escherichia coli: three bases following the stop codon crosslink to release factor 2 and affect the decoding efficiency of UGA-containing signals. - Poole, E S (1998)
The observations that the Escherichia coli release factor 2 (RF2) crosslinks with the base following the stop codon (+4 N), and that the identity of this base strongly influences the decoding efficiency of stop signals, stimulated us to determine whether there was a more extended termination signal for RF2 recognition. Analysis of the 3' contexts of the 1248 genes in the E.coli genome terminating with UGA showed a strong bias for U in the +4 position and a general bias for A and against C in most positions to +10, consistent with the concept of an extended sequence element. Site-directed crosslinking occurred to RF2 from a thio-U sited at the +4, +5 and +6 bases following the UGA stop codon but not beyond (+7 to +10). Varying the +4 to +6 bases modulated the strength of the crosslink from the +1 invariant U to RF2. A strong selection bias for particular bases in the +4 to +6 positions of certain E. coli UGANNN termination sites correlated in some cases with crosslinking efficiency to RF2 and in vivo termination signal strength. These data suggest that RF2 may recognise at least a hexanucleotide UGA-containing sequence and that particular base combinations within this sequence influence termination signal decoding efficiency.